Fascinating stories of forgotten lives : rediscovering some Old Testament characters - Swindoll, Charles R. (Nashville, Tenn. : W Publishing Group, 2005)
"Portrait of twelve lives from the Old Testament whose lives have great lessons to teach us"--Provided by publisher.
Includes bibliographical references (p. 249-251).
Keywords: Bible; Biography; Christian life